Production Performance of Holstein Friesian Cows Under Libyan Conditions : Corrected and Daily Average Milk Production - Zaied, A.A.; kharoofa, A.D.S.; Ahmed, M-K.A.; Salhab, S. A. (Al-Mukhtar Journal of Sciences, 1995)
A total of 2953 production records from Ghot Al-Sultan dairy cattle unit were used. The differences between foreign and local management in addition to some general environmental factors on 3X305 , 2X305 and average daily milk production were studied. The results showed the existence of significant differences (P<0.01) between the two regimes of management for all three traits and in the first two lactations. The 2X305 milk production for the three lactations was 6657.7 +30.7, 7740.250.0 and 7922.767.1. Least squares means for 3X305 milk productuion were 8018.7+37.0,9108.9458.7, 9112.5+77.3 kg. Daily average was 24.8+0.13 , 29.0+0.21 , and 28.8+0.26 for the three lactations consecutively. In addition, seasons within years effects were significant (P<0.05) for both 3X305 and 2X305 production in the third lactation. The effect of the linear regression on age at calving was significant (P<0.01) in the second lactation for 3X305 and 2X305 production. Linear regression on months of the year was significant (P<0.01) in the first lactation only for the three traits.